The Pitfalls of National Consciousness as Depicted in Matigari by Ngugi wa Thiong’o - Athiemoolam, Logamurthie (Journal of Language and Literature, 2018)
The paper provides insights into how national consciousness is eroded in post-colonial Africa with reference to Matigari by Ngugi wa Thiong’o and the impact of this erosion on the marginalized, largely impoverished masses, who continue to live on the periphery of society. The African elite (bourgeoisie), who are the new rulers after colonialism, become so obsessed with their own material enrichment and their new found power, that the ‘imagined state’, for which so many had fought and sacrificed their lives, becomes a mere pipe dream. It is with this background in mind that the paper intends to examine how the pitfalls of national consciousness highlighted by Fanon in his text ‘The Wretched of the Earth’ find resonance in Ngugi’s non-fiction work Matigari and the crucial issues that the text raises in terms of how the new rulers abuse their power and the mechanisms that they implement to entrench their authority. Through Ngugi’s use of the fictional protagonist Matigari, we are taken on a journey that unearths the rampant corruption and brute force of the regime as they strive to annihilate any opposition that dare question their abuse of power.  Keywords: Post-colonialism, National consciousness, Othering, Oppressive regime